Effects of weight loss on metabolic syndrome in severely obese men without diabetes - Dmitrović, Aleksandra M; Jovanović, Luka J; Tančić-Gajić, Milina (Medicinski podmladak, 2017)
Introduction: Obesity is a chronic metabolic disease, characterized by an increased accumulation of fat in adipose tissue, to the extent that damages health and leads to the development of numerous complications. The increasing distribution of obesity has caused a large increase in the incidence of metabolic syndrome. Metabolic syndrome comprises a set of related risk factors for cardiovascular diseases and type 2 diabetes. The basis of therapeutic modalities of obesity make diet, exercise and lifestyle changes. The aim: To assess the effect of reduction of body weight, performed by therapeutic lifestyle intervention, in the sample of extremely obese men without diabetes, on components of the metabolic syndrome and metabolic syndrome itself. Material and Methods: Prospective study included 38 extremely obese men (mean age 41.68 ± 11.93 years, mean weight 142.08 ± 20.11kg, mean BMI 45.90 ± 5.65kg / m2). Anthropometric parameters and blood samples for biochemical analysis were measured before and after the reduction of body weight using therapeutic program, which included a very low calorie diet (VLCD) and low calorie diet (LCD) with physical activity. The relationship between variables was tested by Student’s t-test and Wilcoxon’s rank-sum test. Results: Highly statistically significant reduction was found in waist circumference, systolic and diastolic blood pressure and triglyceride levels (p